2021
DOI: 10.3390/agronomy11112185
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the Kinetics of Color and Texture Changes of Dabai (Canarium odontophyllum Miq.) during Blanching

Abstract: Dabai (Canarium odontophyllum Miq.) is a fruit that is often eaten by first blanching in hot water to make the flesh creamier and softer, before it is served as a snack or side dish. In this study, Dabai fruit was blanched at different temperatures between 60 and 100 °C, with an increment of 10 °C, for up to 10 min, and the kinetics of quality changes (color and texture) were studied. Kinetic models that were assessed for changes of color and texture were zero-order, first-order, and fractional conversion mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The list of published data on the kinetics of texture degradation of some fruits and vegetables were listed in Table 3. Numerous studies were performed focusing on the kinetic models of the texture degradation due to the blanching treatment including the Irish York cabbage (Jaiswal et al, 2012), pumpkin (Gonçalves et al, 2007), carrot (Gonçalves et al, 2010), broccoli (Gonçalves et al, 2009), green beans ((Ruiz-ojeda & Peñas, 2013) and dabai fruit (Shamsudin et al, 2021). Most of the published studies indicated that the texture changes during blanching treatment follow the first-order degradation kinetics (Jaiswal et al, 2012;Ruiz-ojeda & Peñas, 2013).…”
Section: Texturementioning
confidence: 99%
“…The list of published data on the kinetics of texture degradation of some fruits and vegetables were listed in Table 3. Numerous studies were performed focusing on the kinetic models of the texture degradation due to the blanching treatment including the Irish York cabbage (Jaiswal et al, 2012), pumpkin (Gonçalves et al, 2007), carrot (Gonçalves et al, 2010), broccoli (Gonçalves et al, 2009), green beans ((Ruiz-ojeda & Peñas, 2013) and dabai fruit (Shamsudin et al, 2021). Most of the published studies indicated that the texture changes during blanching treatment follow the first-order degradation kinetics (Jaiswal et al, 2012;Ruiz-ojeda & Peñas, 2013).…”
Section: Texturementioning
confidence: 99%
“…The best mixture of 37% of total fruit puree with a 1:1 watermelon to dabai fruit ratio, 8% sugar, 0.1% pectinase enzyme, 0.1% citric acid, 0.05 sodium benzoate, and 54.75% water had a shelf life of 3 weeks. A paste made from the creamy fresh or preserved flesh of the dabai fruit is the main component of a savory stir-fried rice with dabai [ 61 ].…”
Section: Potential Of Food Products and Essential Oil Processing Of D...mentioning
confidence: 99%
“…One of Sarawak’s native fruits, the dabai, was recently determined to have significant potential for commercial exploitation. Dabai is a highly perishable crop, and few organizations have started shelf life studies on the preservation or minimization of quality loss [ 61 , 66 , 67 ]. The marketing life of dabai has been limited by its short shelf life.…”
Section: Future Perspective and Challengesmentioning
confidence: 99%
“…After the blanching process, it is important to observe the quality of the dabai fruit in terms of color and firmness to avoid under-blanching and over-blanching. It is because under-blanching can speed-up enzyme activity, while over-blanching can cause degradation of texture and color (Ruiz-Ojeda & Peñas, 2013;Shamsudin et al, 2021). There has been little study on the effect of blanching conditions, including temperature and the duration of blanching that can retain the quality of the dabai fruits, which have yet to be determined.…”
Section: Introductionmentioning
confidence: 99%